(untitled) (Iraqi Journal of Civil Engineering, 2024)
Microbial-induced carbonate precipitation (MICP) is a fast-evolving technology for cementing sandy soils, improving ground, repairing concrete cracks, and remediating contaminated land. The current work thoroughly reviews various factors that can impact the effect of the MICP technology on geomaterials. These factors include the type and strain of the microbes, concentration of bacterial solution, cementation solution composition and concentration, environmental factors (temperature, pH level, and oxygen dissolved), and soil properties. It was found that the type and strain of bacteria, concentration of bacterial suspension, pH value, temperature, and the reaction solution properties are the most affecting factors in controlling the characteristics of the produced calcium carbonate, which in turn affects the degree of bonding between geomaterials particles. For an optimal implementation of the MICP in soils treatment, it appeared that for the most commonly used bacterial strains a temperature between 20 and 40 °C, a pH between 6.5 and 9.5, and a cementation solution concentration of 0.5 mol/L, are typically recommended.